Doctor and patient’s relationship at the present time and value of the clinical method - Orlando Cruz Martínez; María Caridad Fragoso Marchante; Iris González Morales; Dianelys Perla Sierra Martínez (Medisur)
The history of mankind is not only made of the relationships and conflicts among men: the struggle to survive is also part of it and the hardest and most persistent of all has been men’s fight against diseases. The emergence of medical activity is inextricably linked to the development of human relationships. In fact, it is precisely the capacity of establishing relationships with others what identifies and distinguishes man from other biological beings. The recognition of the values of the doctor-patient relationship and its psychological moment is gnoseologically attached to the recognition of the values of the integral vision of man. That is why the Hippocratic school, constantly insisting that man is not only the physical aspect, but an inseparable whole with the psychic aspect and emphasizing on the importance of the environment and the doctor-patient relationship constitutes a milestone in the development of medicine. Over the centuries much has been learned and even more has been written about this unique kind of human relationship that causes everyday a renewed interest not only for medicine but also for many adjacent disciplines, as a sign of its decisive importance and the socio-historical conditions that determine it.